Effects of synthetic pyrethroids Cyfluthrin and Fenvalerate on Nucleic acid contents of fresh water fish Gambusia affinis - Ghouse, S. Mohammed (International Journal of Scientific Research in Biological Sciences, 2019)
India is a country with more than 60–70% of its population dependent on agriculture. Rapid industrialization and successful green, white and blue revolutions have necessitated a large variety of chemicals/pesticides usage resulting environmental pollution which has become not only a national but a global problem. Fish occupy a prominent position in the field of aquatic toxicology and have been employed in studies concerning ecological health. In the present investigation two synthetic pyrethroids were selected namely Cyfluthrin and Fenvalerate to evaluate their toxicity on Gambusia affinis. In the present study there is significant decline in DNA content in the gill, liver and kidney tissues is observed, when the fish Gambusia affinis is exposed to the cyflthrin and fenvalerate. Decreases in the DNA content due to inhibition of the enzymes in DNA synthesis. The declines in RNA level in treated fish due to obstruction in RNA synthesis. Resulting in the swelling and chromatolysis of Nissle bodies which are rich in RNA. Pesticides may influence directly or modify DNA, other cellular process associated with the integrity of the genome.